Implementation of the BRIDGE Multicultural Leadership Model to Enhance School Inclusivity at Palalangon 2 Public Elementary School, Ciranjang Subdistrict, Cianjur Regency, West Java Province - Riska Irnawati; Wiwin Awaliyah; Sunsun Pradana Yogaswara; Dadang D; Hendi Fauzi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The diversity of religions, cultures, and social backgrounds in school environments requires leadership that can manage differences constructively in order to build an inclusive educational environment. However, studies on multicultural leadership models based on the practical leadership of school principals in plural elementary school contexts remain relatively limited. This study aims to analyze the implementation of the BRIDGE multicultural leadership model in improving school inclusivity. The research employed a qualitative approach using a case study method at SD Negeri Palalangon 2, Cianjur Regency. Data were collected through interviews, observations, and documentation, and then analyzed using the interactive analysis model of Miles and Huberman. The findings indicate that the implementation of the BRIDGE model—comprising the dimensions of Balanced Perspective, Respect, Interaction, Dialogue, Growth, and Empowerment—can foster a school culture that values diversity, strengthen cross-cultural communication, and enhance collaboration between the school and the community. The novelty of this study lies in the development of the BRIDGE multicultural leadership model as an integrative and contextual leadership framework for managing social diversity in elementary schools. This model contributes conceptually to the development of multicultural educational leadership studies while also offering a practical approach to building inclusive schools.